Pengaruh Manajemen Laba Pada Agresivitas Pajak dan Implikasinya Terhadap Nilai Perusahaan - Diatmika, Made Dika; Sukartha, I Made (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
This study aims to determine the effect of earnings management on tax aggressiveness and its implications for firm value. This research was conducted at mining companies listed on the Indonesia Stock Exchange in 2012-2017. The data analysis technique used is path analysis. Based on the results of path analysis, it is known that earnings management with decreasing income has no effect on tax aggressiveness. Tax aggressiveness has a negative effect on firm value. Earnings management with income decreasing has a negative effect on firm value. Earnings management with decreasing income does not influence indirectly on firm value through tax aggressiveness. The implication of this research theoretically is supporting agency theory and signal theory while practically this research can provide a positive contribution to all parties, especially companies, the main users of financial statements, and also the government. Keywords: company value, earnings management, tax aggressiveness